POP PUNK COMMUNITY GROUP COMMUNICATION IN MAINTAINING COHESIVITY IN PEKANBARU - Fichry Abdillah; Nova Yohana (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2021)
The punk genre in Indonesia initially imitated music as well as lyrics with the theme of resistance, but the lyrics of this punk music have a different context from the background of problems in Indonesia. In Pekanbaru itself, Pop Punk has entered and developed in 2008 because it was delivered by several communities. The Covid 19 pandemic makes art workers and communities have to survive and also innovate to stay afloat, ways to maintain cohesiveness will change and events that were initially delayed due to the Covid 19 pandemic, before that, how to introduce groups that were initially small to large was influenced With fashion and music, Pop Punk Pekanbaru has grown rapidly in the music community in Pekanbaru. In this way there is a process of communication patterns in the Pekanbaru pop punk community, which consists of the role of communication actors, the messages that are exchanged, the interactions that occur in the group communication process, group norms and cohesiveness. From the phenomenon that is currently happening in the music scene in Pekanbaru, the writer is interested in researching the Pekanbaru Pop Punk Community Communication. This research uses qualitative research methods with a qualitative descriptive format model. The research informants consisted of six people, of which six informants were the main informants. Data collection techniques consist of interviews, observation, documentation. While the data analysis technique is to use descriptive analysis techniques. For data validity checking techniques, participation extension and triangulation were used. Based on the results of the research conducted by the author, the research results obtained. The role of group communication actors is inseparable from the role of the chief advisor and treasurer in the Pekanbaru pop punk community. Message exchange in the Pekanbaru Pop Punk community includes verbal and non-verbal messages, Communication in the Pekanbaru Pop Punk community. is two-way communication, either through face-to-face or through WhatsApp groups. In the Pop Punk Pekanbaru community, the norms used are the norms that develop throughout society and the cohesiveness that is formed in this group is more or less influenced by the existence of communication interactions that occur intensively and also habits.